The complete bibliography of scientific works of Jacques-Marie-Frangille Bigot - Evenhuis, Neal L. (Zootaxa, 2003)
A complete bibliography of scientific works of the dipterist, Jacques-Marie-Frangille Bigot, is presented in chronological order with accurate dates of publication. A total of 411 works are listed including taxonomic works, reviews of the works of colleagues, errata, and other types of articles.